Sentinel lenf nodu biyopsisinde yanlış negatiflik oranı nasıl belirlenir? - (:unkn) unknown (My University, 2008)
0
How to calculate the false negativity rate for sentinel lymph node biopsy procedure?
Keywords: Cerrahi